Patient's knowledge, gender, and physical activity level as the predictors of self-care in heart failure patients - Mifetika Lukitasari; Ulfia Fitriani Nafista (PAGEPress Publications, 2023)
Introduction: Self-care management is the fundamental approach for Heart Failure (HF) management and is influenced by patient ability in preventing rehospitalization, mortality, and morbidity. Therefore, this study aims to investigate the predictors of a patient's ability in HF self-care management. Design and Methods: A cross-sectional study was carried out on 96 patients with HF. The data were collected through interviews using questionnaires on demographic characteristics, physical activity (IPAQ), knowledge (Dutch Heart Failure Knowledge Score), and self-care management (Self Care Heart Failure Index). Subsequently, the data were analyzed using logistic regression analysis, and the best fit model for predicting self-care management in HF patients was generated. Results: The proportion of samples was 56.3% female, with mostly primary school (50%) as their education level. Furthermore, the proportion of patients with adequate HF self-care management was only 21% of the total participant. Based on the results, the patient's physical activity level, HF knowledge, and gender were verified as a predictor of self-care management. Conclusions: The HF knowledge level, physical activity level, and gender were the predictors of HF self-care management.